WELLBEING - AN IMPORTANT DIMENSION OF TEACHING-LEARNING - Mihaela Aurelia ŞTEFAN (Universitaria Publishing House, Craiova, 2024)
One of the most important tasks of the teacher is to build positive interpersonal relationships and thus generate a positive socio-emotional climate. The study aims to emphasize the importance of the emotional dimension of teaching learning. Starting from the premise that wellbeing is a conditional factor of academic success, we focused, in this material, both on theoretical aspects related to wellbeing as an axis of teaching-learning, as well as on the results of an investigative approach regarding the state wellbeing of students in teaching learning activities. The questions that stood out to us were the following: How much importance do students attach to wellbeing? To what extent are teachers concerned about the wellbeing of students? To what extent does the school teach students to focus on positive experiences and overlook negative ones? What are the students' suggestions regarding the main directions of action that can lead to student wellbeing in the classroom? Based on the processing and interpretation of the data collected through the application of a questionnaire, the recorded conclusions allowed the identification of some aspects regarding the importance of students' wellbeing in teaching activities, but also their suggestions with reference to building an educational climate focused on wellbeing. The research data demonstrated that the emotional, affective-motivational dimension is as important as the (meta)cognitive one. Wellbeing is essential in the didactic activity. Students' negative thoughts and emotions can be shaped, restructured, by building an environment focused on wellbeing that allows optimal and balanced adaptation to diverse situations.